2013
DOI: 10.1007/s00384-013-1707-8
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of lymph node ratio in colon and rectal cancer: not one size fits all

Abstract: Application of a data-driven approach based on recursive partitioning generates differing lymph node ratios for colon, rectal and combined colorectal cohorts. In each cohort, LNR was similarly prognostic to standard nodal staging in respect to overall and disease-free survival. Overall survival was associated with a multiplicity of LNR values, whilst disease-free survival was associated with a single LNR only. The paper demonstrates the merits of utilising a data-driven approach to determining lymph node ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…So far, LNR cut‐off values vary in studies due to different statistical methodologies used to generate the ratio. Other than the robust mechanism for generating LNR reported by Medani et al, studies in our current meta‐analysis reported mainly median values or receiver operating characteristic (ROC)‐based values as the best cut‐off values (three studies used median LNRs as the cut‐off, another three adopted ROC curve analysis‐based LNR cut‐offs, one study used interquartile range, one study used a novel method with Maxstat, one study chose the best cut‐off based on other standards, and one study recommended 0.25 as the cut‐off value for the reason that 0.25 represents the number of metastatic LN of pN1 category based on 12 LNs harvested). Additionally, the remaining three studies generated the cut‐offs arbitrarily without declaring any data‐driven approaches.…”
Section: Discussionmentioning
confidence: 99%
“…So far, LNR cut‐off values vary in studies due to different statistical methodologies used to generate the ratio. Other than the robust mechanism for generating LNR reported by Medani et al, studies in our current meta‐analysis reported mainly median values or receiver operating characteristic (ROC)‐based values as the best cut‐off values (three studies used median LNRs as the cut‐off, another three adopted ROC curve analysis‐based LNR cut‐offs, one study used interquartile range, one study used a novel method with Maxstat, one study chose the best cut‐off based on other standards, and one study recommended 0.25 as the cut‐off value for the reason that 0.25 represents the number of metastatic LN of pN1 category based on 12 LNs harvested). Additionally, the remaining three studies generated the cut‐offs arbitrarily without declaring any data‐driven approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Medani et al . have previously suggested that a data‐driven approach is needed to determine the cut‐off point for the LNR. By setting the specificity, the present study addressed this by using comparison with current nodal staging to guide determination of the cut‐off point.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while the LNR is predictive of overall survival it does not offer a clinically significant advantage over the current N1/N2 classification. Medani et al [25] have previously suggested that a data-driven approach is needed to determine the cut-off Survival time (months) Figure 1 Kaplan-Meier curves demonstrating that the N1/N2 and LNR1/LNR2 classifications are both predictive of overall survival (P < 0.001 log-rank test). The numbers entering each time interval are given in the tables beneath the Kaplan-Meier curves.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent papers have suggested the usefulness of the lymph node ratio rather than the total number of involved lymph nodes. [47][48][49][50] This is not currently recommended but is an issue that may be considered for staging in the future.…”
Section: Required Number Of Lymph Nodesmentioning
confidence: 99%